A narrative review of nursing in Saudi Arabia: prospects for improving social determinants of health for the female workforce - Davies, Julie; Yarrow, Emily (Frontiers in Public Health, 2025)
IntroductionNurses represent the backbone of global healthcare systems where women typically deliver care and men lead. The Kingdom of Saudi Arabia (KSA) highly relies on foreign female nurses despite Saudisation policies designed to localize its workforce. Yet, in the context of an ambitious 2016–30 national health transformation program to modernize public health in a high-income and rapidly developing country, intersectional inequalities persist for migrant and local nurses in KSA. There are challenges in the specialisms of palliative and end-of-life care where there is a weak public and professional understanding of caring for people with life-limiting diseases and a lack of public discourse about death and dying. In this context, we ask which social determinants of health (SDOH) might be improved for female nurses in KSA to support SDOH improvements in the general population.MethodsBased on a narrative literature review of 36 studies using Cochrane, EBSCO, PubMed, and Web of Science databases, we highlight the social determinants of health and wellbeing for both migrant nurses in PC and general population health.FindingsFour key themes emerged from the literature review related to equity, ability, compassionate support, and meaning in the workplace. We illustrate that key SDOH for female nurses in KSA include inadequate housing, labor market fragmentation; gender, pay, religious, language and racial discrimination against nurses from low and middle-income countries with a general lack of understanding about PC. In turn, we explore these factors within four main themes: equity; ability; compassionate support; and meaningful work. Workforce shortages can result in working shifts and overtime with a lack of flexible working, which in turn cause stress, burnout, precarity, low job satisfaction and high turnover. We identify gaps between national policy ambitions for modernization and everyday practices caring for the Saudi nursing workforce.DiscussionOur review is novel in exploring the social determinants of health in the healthcare workforce linked to social determinants such as housing, income, job insecurity and working life conditions, living conditions, social inclusion and norms and socioeconomic position. It contributes to our understanding of how patriarchal cultures shape institutional and subjective forms of inequality in stark contrast to the national rhetoric of female empowerment. We propose three policy recommendations to improve PC nurses’ SDOH and, in turn SDOH for the general population: (i) gender and race pay equity, (ii) human resource for workforce health and education policies using telehealth, and (iii) professional and public communication campaigns to increase respect for nurses and understanding the benefits of PC nursing as a career and as a service.